Perceptions of oral corticosteroid use for children with asthma in a survey of US caregivers - Ramirez, Nina C.; Hernandez-Trujillo, Vivian; Sumino, Kaharu; Williams, Dennis; Patel, Mitu; Gardner, Donna D. (Frontiers in Pediatrics, 2025)
IntroductionOral corticosteroids (OCS) are an essential component of asthma treatment, but their long-term effects can be serious and cumulative. Potentially serious effects include adrenal suppression and psychological effects. To mitigate side effects, OCS use should be minimized. A survey of caregivers in the US was conducted to determine their perceptions of OCS use for their child with asthma.MethodsIndividuals who participated in US consumer research panels were invited to complete an online cross-sectional survey from October-November 2023. Eligible participants were caregivers of a child ages 6–17 years currently being treated for asthma by a healthcare provider and who had experienced an asthma attack, flare or exacerbation (AAFE) in the past 12 months.ResultsCaregivers (N = 500) were racially and ethnically diverse (4% Asian, 18% Black, 63% White, 20% Hispanic/Latino). Responses indicated that 92% of caregivers' children had uncontrolled asthma. In the past 12 months, children were treated an average of 3.6 times for AAFE and received at least 3 OCS prescriptions. Overall, 61% of caregivers believed their child would be sick longer when having an AAFE if not treated with an OCS; 92% believed their child's asthma symptoms improved at least a moderate amount with OCS. In all, 69% and 54% reported familiarity with short-term and long-term side effects of OCS, respectively. Caregivers perceived OCS as relatively safe for their child. The most common short-term OCS side effect experienced by their child was mood changes. Caregivers were most concerned about mood changes and cardiovascular disease as short-term and long-term effects of OCS, respectively.ConclusionsOCS therapy is often used for AAFE and is perceived by caregivers as effective and safe. Caregivers and healthcare providers should be educated about side effects and the importance of optimizing asthma treatment to reduce OCS use.